Fluctuations Mitigation of Variable Speed Wind Turbine through Optimized Centralized Controller - Ali Mohammadi; Sajjad Farajianpour; Saeed Tavakoli; S. Masoud Barakati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
A wind energy conversion system (WECS) including a variable wind turbine in grid-connected mode is considered to control. In this paper, each component of WECS model is systematically presented and then the integrated overall model is validated.Regarding to nonlinear nature of WECS and the complex system structure as multiple-input multiple-output (MIMO), it is difficult to find a proper control strategy. To simplify the control design, a centralized controller, which is compatible with systematic modelling, is employed. In addition, to enhance the centralized controller performance, an optimization based on genetic algorithm (GA) is accomplished. Simulation results demonstate the effectivesness of the proposed control startegy to mitigation fluctuations.